How to simplify and improve incident and near miss reporting in wards: I.R.G.E. (Incident Reporting with Gravity Effect) system (Italian Journal of Public Health, 2011)
In this paper, an improved system that allows a simplified reporting of errors and near misses in wards,and permits operators to accurately manage all data recorded, is presented. IRGE (Incident Reporting withGravity Effect) System is based on the use of a paper form for reporting accidents and near misses. Theseverity of an error can be evidenced through the choice of a color similar to the well-known method usedin the emergency medicine triage, thus leading to the most evident and immediate understanding of themagnitude of error. In addition, the system is provided with a report form for its users to be compiled withthe highest completeness of information.A dedicated software for the storage of records and data analysis has been created, which gives one thepossibility of alerting key figures within the health facility promptly. The system allows us to store and sharerecords among different care units and also among different hospitals, thus providing a basis for a nationaldatabase. Moreover, through this system, it is possible to assess the “risk attitude” of the health facilitymonitored.
Keywords: error; near miss; incident reporting system; risk management